(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2022)
The present work deals with the impact of the change from face-toface to virtuality in the face of the Covid-19 pandemic as a driver of ICTs in higher education, in which everything related to the use of ICTs will be shown and how currently they are being the protagonists of the activities in higher education so that it can continue its course in the midst of the pandemic, the measures taken to safeguard the safety of the entire university community by its authorities will be shown, one of them is confinement or forty to prevent their community from being exposed to Covid-19 contagion and so that academic activities can continue, it was decided to make use of ICTs in a very significant way since it is currently the most feasible way, we will have concepts, data both of Covid-19, ICTs, Higher Education, as well as the use of ICTs. In this work we can also find surveys carried out on both students and teachers about ICTs in higher education in quarantine, we will indicate our appreciation of the academic processes and the benefits of the use of technologies.